Score prediction on kips performed on the parallel bars - Prassas, S.; Ariel, G.; Ostarello, J. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
INTRODUCTION: Kips are performed by both male and female gymnasts in a variety of apparatus including the parallel bars. Althought kips are considered to be one of the fundamental skills in gymnastics, research is scarse (Prassas, 1993). The purpose of this study was to investigate the factors that influence the score awarded to kips performed on the parallel bars by qualified judges. METHODS: Eighteen kips performed by elite gymnasts were recorded utilizing a NAC 400 high-speed video camera operating at 100 Hz. The analysis was performed using the Ariel Performance Analysis System (APAS). Two-dimensional position data of four (kips performed without knee and/or elbow joint flexion) to six (kips exhibiting knee and/or elbow joint flexion) body points were digitally smoothed with a cut off frequency of 6 Hz before submitted to further analysis. The analyzed kips were rated by two internationally qualified judges on a scale ranging from 1 (worst) to 10 (best). SigmaStat 3.5 (SYSTAT, Inc.) software was used for statistical analysis. RESULTS AND DISCUSSION: Preliminary regression analysis results suggest that the judges' score variation can be predicted